Study the lighting in higher learning spaces / Athirah Fatini Mohd Ashari - Mohd Ashari, Athirah Fatini (2022)
Lighting previously has been found affecting people’s comfort, productivity, and health. The lack of proper indoor lighting comfortability in learning rooms can have a significant impact on student ability to focus on their learning. This study provides a comprehensive summary of the literature on the impact of indoor lighting on student productivity and visual comfort in higher learning spaces. This research findings show that improving lighting in learning spaces is significant for enhancing student concentration and motivating them to learn more. The survey questionnaire is the method used to find out how lighting affects students learning abilities. The information was gathered through a survey consists of students from UiTM Shah Alam and Puncak Alam to determine their satisfaction with the current indoor lighting quality. The findings of this study will serve as guidance for management efforts to improve the indoor lighting design in higher learning spaces.